Simplify the expressions and evaluate them as directed:
(i) x(x – 3) + 2 for x = 1 (ii) 3y(2y – 7) – 3(y – 4) – 63 for y = –2.
Simplify (a + b) (a - 2b + 3c) - (2a - 3b)c
∵ (a + b) ( a - 2b + 3c) = a x ( a - 2b + 3c) + b(a - 2b + 3c)
= a2 - 2ab + 3ac + ab - 2b2 + 3bc
= a2 + (- 2ab + ab) + 3ac - 2b2 + 3bc
= a2 - 2b2 - ab + 3bc + 3ac
and ( 2a - 3b) x c - 2ac - 3bc
∴ ( a +b) (a - 2b + 3c) - (2a - 3b) x c
= (a2 -2b2 - ab + 3bc + 3ac) - (2ac + 3bc)
= a2 -2b2 - ab + (3bc + 3ac) - (2ac + 3bc)
= a2 -2b2 - ab + 3(bc + 3ac) + (3ac + 2ac) ( Combining the like terms bc and ac)
= a2 -2b2 - ab + (6bc) + (ac)
= a2 -2b2 - ab + 6bc + ac
Thus, (a +b) (a - 2b + 3c) - (2a - 3b)c = a2 -2b2 - ab + 6bc + ac